KIDNEY DISEASES AND THEIR PATHOGENESIS: A SCIENTIFIC OVERVIEW - Yusupova Maftuna Azamatovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Kidney diseases encompass a broad spectrum of disorders affecting the structure and function of the kidneys. Understanding the pathogenesis of these diseases is essential for effective diagnosis, treatment, and prevention. This article reviews common kidney diseases, including glomerulonephritis, diabetic nephropathy, and chronic kidney disease (CKD), and discusses the molecular and cellular mechanisms underlying their development and progression.